Research on Ground Settlement Regularity of Soft Rock Tunnel under Ultrasmall Distance - Chunwu Zhang; Wei Hou; Zongjun Sun; Li Gu (Advances in Civil Engineering, 2021)
During the tunnel construction under the road, the shallower the tunnel depth, the greater the effect of the surface settlement. Thus, to analyze the ground settlement caused by tunnel construction under ultrasmall distance, the research is based on a tunnel in Ningqiang County and uses numerical simulation and measurement to analyze the ground settlement and the effect of reinforcement measures. The research draws the following conclusions. For the ultrasmall distance tunnel under road construction, the combination of pipe shed and advanced small pipe grouting reinforcement measures inhibits the surface settlement. After the advanced small pipe is reinforced, the surface settlement value is reduced by about 25%, and the reinforcement effect is more obvious after the increase of the large pipe shed. The surface settlement value is reduced by about 60%. The surface settlement caused by the excavation of the circular soil accounts for about 50%–60% of the total settlement value, which is for the whole construction. The key processes, which involve the combination of reinforcement measures, focused on the suppression of surface settlement caused by the excavation of the circular soil. After the reinforcement measures, the variation of the settlement groove width was not obvious but the curvature and peak value of the settlement groove is reduced significantly.